One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design